Adding Acoustical to Visual Movement Patterns to Retest Whether Imitation Is Goal- or Pattern-Directed. Issue 1 (February 2020) - Ramezanzade, Hesam
This study compared two different motor skill modeling presentations (with and without goal display) in visual and audio-visual conditions for learning a complex skill (basketball jump shot) to evaluate the importance of (a) audio information and (b) goal observation in motor performance kinematics. Specifically, we sought to understand whether the simultaneous presentation of auditory and visual patterns could usefully direct the learner's attention from goal to pattern stimuli. I selected 40 students ( M age  = 20.47 years) who had no prior experience with the basketball jump shot or free throw and randomly assigned them into four groups: Pattern/Visual, Pattern/Audio-Visual, Pattern-Goal/Visual, and Pattern-Goal/Audio-Visual. Participants in the pattern-only groups watched only the skilled motor pattern, while those in the pattern-goal groups watched both the pattern and its outcome. Participants in the visual-only groups simply watched the visual pattern, while those in audio-visual groups saw and heard the pattern; we sonified the angular velocity of the skilled performer's elbow joint. Participants then performed in two conditions with and without balls. On all dependent variables, the participants' performance following the audio-visual presentations was better than when following the visual-only presentations. In addition, the participants' performance in pattern-only groups was better than in pattern-goal groups, but this improved pattern-only performance was far less extensive in the audio-visual than in the visual-only group. In sum, complex motor skill imitation was enhanced by an audio pattern of elbow angular velocity in support of generalist theories of imitation learning.